Digital Transformation of Financial Literacy and Inclusion as a Support for Convenience for MSMEs - Restu Millaningtyas; Moh. Amin; Agus Hermawan; Puji Handayati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Financial digital transformation provides easy access to financing in terms of financial literacy and inclusion. Digital financial literacy and inclusion is a means of education and ease of life and the future for both personal and business needs that are financially effective and efficient in various aspects including a wider range of transactions, easy to use, time-saving, affordable costs, easy-to-understand tools and maintained security. The purpose of this article is to explain the digital transformation of financial literacy and inclusion, explain the contribution of digital financial literacy to the convenience of MSMEs, explain the contribution of digital inclusion to MSMEs and discuss the advantages, disadvantages and solutions of digitalization of financial literacy and inclusion in its implementation. The method used in the study is RISMA 2020 (Preferred Reporting Items for Systematic review and Meta-Analyses) aimed at increasing the transparency and completeness of reporting systematic review results making it easier for readers to assess the trustworthiness and applicability of review findings. The result of digital transformation is financial access and financial literacy providing convenience through an easy-to-use and secure financial service platform for both the general public and business owners in conducting transactions, financing and investment. Digitalization of financial literacy will facilitate financial access, get financial education, and facilitate transactions, but in some countries financial inclusion does not have a significant effect on alleviating MSMEs, if these countries provide policies to financial institutions to increase lending with easy collateral it will enable the success of MSMEs.